مفردات المالكية في باب الأضحية - قسوم مدني (University of Eloued جامعة الوادي, 2024)
"قد أخد اختلاف العلماء في مسائل الفقه أشكالا متنوعة, ومن أهمها وأبرزها: أن يكون الخلاف بين الجمهور ومذهب من المذاهب الأربعة, وهو ما يسمى بالمفردات الفقهية, فاخترت أن أتحدث في هذا البحث عن باب من أبواب الفقه, وهو باب الأضحية, والمسائل التي تفرد بها المالكية فيها عن غيرهم من المذاهب الثلاثة, فسطرت خطة من مطلبين أفصحت فيهما عن المفردات من حيث تعريفها وتاريخ التأليف فيها, ثم الأضحية والحكمة من تشريعها؛ ثم خصصت مطلبين آخرين تطرقت فيهما إلى مسائل عدة؛ بعضها متعلق بعين الأضحية, وبعضها بصفة الذبح, وبعضها بالمضحي, وآخرها بوقت التضحية. كانت خلاصة بحثي: أن تفرد المالكية ليس ضربا من الشذوذ الفقهي, وإنما هو خلاف مبني على أصول, وأدلة معتبرة, وأن ما تفردوا به في باب الأضحية ترجح قول الجمهور في بعضها. The differences between scholars on jurisprudential matters have taken various forms, and among the most important and prominent of these is the disagreement between the majority and one of the four schools of thought, which is called jurisprudential specifics. Therefore, I chose to discuss in this research a chapter of jurisprudence, which is the chapter on Udhiyah (sacrificial offering), and the issues in which the Maliki school is distinct from the other three schools. I outlined a plan in two sections where I clarified the specifics in terms of their definition and the history of their compilation, then the Udhiyah and the wisdom behind its legislation. I then dedicated two other sections to various issues; some related to the sacrificial animal itself, some to the manner of slaughter, some to the person performing the sacrifice, and last one to the time of sacrifice. The conclusion of my research was that the distinctiveness of the Maliki school is not a form of jurisprudential anomaly, but rather a disagreement based on established principles and credible evidence, and that in some issues related to Udhiyah, the view of the majority is more favorable "
ماستر
Keywords: المفردات؛ المالكية؛ الأضحية؛ الذبائح؛ وقت التضحية.; Vocabulary; Al-Malikiyah; The sacrifice characterization; sacrifices; Time for sacrifice